2011
DOI: 10.1007/s11886-011-0215-0
|View full text |Cite
|
Sign up to set email alerts
|

What is the Ideal Blood Pressure Goal for Patients with Stage III or Higher Chronic Kidney Disease?

Abstract: Hypertension and chronic kidney disease (CKD) are public health problems well known to the national and international medical communities. Blood pressure (BP) control in patients with CKD stage III and IV plays a key factor in reducing cardiovascular risk and renal disease progression. We conducted a literature review of recent studies addressing BP targets and cardiorenal outcomes in patients with CKD. Multiple studies demonstrated cardiovascular benefits associated with greater BP reduction. Nevertheless, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…57 In this patient population, hypertension itself is a leading cause of renal failure. BP goals in patients with CKD and microalbuminuria are lower than in the general population, 22,58 with a target the same as that in patients with established CAD. Recent investigations have demonstrated that standard treatments for cardiovascular risk factors, including statin therapy, ACE inhibitors, ARBs, and antiplatelet agents, are equally effective at risk reduction in patients with CKD (who are not on dialysis) as in those without CKD and should be offered to this patient population.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…57 In this patient population, hypertension itself is a leading cause of renal failure. BP goals in patients with CKD and microalbuminuria are lower than in the general population, 22,58 with a target the same as that in patients with established CAD. Recent investigations have demonstrated that standard treatments for cardiovascular risk factors, including statin therapy, ACE inhibitors, ARBs, and antiplatelet agents, are equally effective at risk reduction in patients with CKD (who are not on dialysis) as in those without CKD and should be offered to this patient population.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…Every CKD and end-stage renal disease (ESRD) patient is almost inevitably a cardiac patient with several issues to be considered [36]. From the point of view of the kidneys, the main task is the reduction of CKD progression through the control of intraglomerular hemodynamics and hyperfiltration, the limitation of protein and salt intake, neurohormonal modulation, and control of blood pressure [37]. Recent evidence has pointed out that chronic inflammation, anemia, and metabolic alterations typical of uremia (e.g., hyperuricemia) [38,39] even at its early stages may influence the rate of vascular calcification, myocardial fibrosis, aortic and mitral calcification, and the propensity for atrial and ventricular arrhythmias [40,41].…”
Section: Crs Typementioning
confidence: 99%